2015
DOI: 10.1016/j.jns.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Are white matter abnormalities associated with “unexplained dizziness”?

Abstract: IntroductionAlthough cerebral small vessel disease is a significant contributor to the development of imbalance and falls in the elderly, whether it causes dizziness is not known.MethodsA retrospective case analysis was conducted for 122 dizzy patients referred to two neuro-otology tertiary centres in London and Pisa. Patients were divided into ‘explained’ causes of dizziness (e.g. benign positional vertigo, vestibular neuritis, orthostatic hypotension, cerebellar ataxias) and ‘unexplained’ dizziness. White ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 17 publications
(20 reference statements)
3
43
0
5
Order By: Relevance
“…A contribution of WML as verified by MRI to the occurrence of vertigo was also suggested by a study of patients with visual vertigo [ 20 ]. Another study found a higher frequency of severe WML in a patients group with unexplained dizziness compared to a group of explained causes of dizziness [ 21 ]. In addition, there is evidence that dizziness might be more indicative of WML than of silent brain infarcts [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A contribution of WML as verified by MRI to the occurrence of vertigo was also suggested by a study of patients with visual vertigo [ 20 ]. Another study found a higher frequency of severe WML in a patients group with unexplained dizziness compared to a group of explained causes of dizziness [ 21 ]. In addition, there is evidence that dizziness might be more indicative of WML than of silent brain infarcts [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegenerative disorders that affect posture and gait such as Parkinson's disease, cerebellar degeneration [61], including the downbeat nystagmus syndrome [89], and small vessel white matter disease [2,16,66] may manifest with dizziness or unsteadiness when standing or walking before motor signs can be detected on physical examination. The gradual onset of these complaints in the relative absence of difficulties with complex or moving visual stimuli should arouse suspicion that PPPD is not the correct diagnosis.…”
Section: Chronic Neurologic Disordersmentioning
confidence: 99%
“…The symptom complex of subjective unsteadiness and a persistent sensation of light-headedness, without any rotational vertigo-that patients refer to as a vague sense of "dizziness"-is often reported by elderly patients attending neurology or balance clinics [4]. In light of a normal extensive battery of neurological and neuro-otological assessments, the patient's dizziness may be termed "unexplained", a particularly common and challenging problem in the elderly.…”
Section: "Unexplained" Dizziness In the Elderlymentioning
confidence: 99%
“…Ahmad et al sub-divided patients with cSVD into either 'high' or 'low' cSVD burden and identified that over 80% patients with high grades of cSVD suffered from otherwise unexplained dizziness, compared to 48% of patients with low-grade cSVD [4].The implication is that cSVD may be an independent factor in the development of balance and dizziness symptoms in the elderly.…”
Section: "Unexplained" Dizziness In the Elderlymentioning
confidence: 99%